A human case of Streptococcus suis infection caused by an unencapsulated strain. Issue 2 (June 2014) - Kerdsin, Anusak; Takeuchi, Dan; Gottschalk, Marcelo; Hamada, Shigeyuki; Akeda, Yukihiro; Oishi, Kazunori
Abstract : Introduction: Streptococcus suis, an emerging zoonotic pathogen, causes invasive infections in persons who are in close contact with infected pigs or contaminated pork‐derived products. Although serotype 2 is the most prevalent type in S. suis infections in humans, to the best of our knowledge no human case caused by an unencapsulated strain has been reported previously. Case presentation: A 53‐year‐old male alcohol misuser with liver cirrhosis was admitted with sepsis to a hospital in Sukhothai Province, Thailand. He had consumed a homemade raw pork product 3 days prior to the onset of illness. An isolate from blood culture was confirmed as S. suis by species‐specific PCR and 16S rRNA gene sequencing, and as untypeable by a coagglutination test. The absence of a capsule around the bacterial cells was also confirmed by transmission electron microscopy. The isolate was also confirmed as sequence type 28 by sequence typing, and analysis of the capsule locus detected disruption of the cpsE–cpsK region, which comprises an approximately 2.5 kb fragment that contains phosphatase and kinase genes. Conclusion: We have identified the first human S. suis infection caused by an unencapsulated strain in a patient with liver cirrhosis. This unencapsulated strain was attributable to a mutation of the cps gene. Clinicians should be aware of the emergence of S. suis infection caused by unencapsulated strains, especially in patients with liver cirrhosis.